2019
DOI: 10.3897/herpetozoa.32.e35623
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the Rufous Frog Leptodactylus fuscus (Anura, Leptodactylidae) from two contrasting environments

Abstract: The impact of urbanization on amphibians has received some attention in the conservation literature. Despite the various impacts on animal life, some species can persist along the cities structures by adjusting their natural histories. Leptodactylusfuscus is a common anuran species occurring in South America, which can commonly be found in urban environments. Herein, we compare the diet of L.fuscus between an urban and a wild environment. We collected 57 individuals of L.fuscus and analysed their diet, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Most amphibians are generalist and opportunistic invertebrate feeders (Balint et al ., 2008; Crnobrnja-Isailovic et al ., 2012; Kittel and Sole, 2015; Do Couto et al ., 2018; Santana et al ., 2019). However, some species are specialist predators (Menin et al ., 2015; Do Couto et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most amphibians are generalist and opportunistic invertebrate feeders (Balint et al ., 2008; Crnobrnja-Isailovic et al ., 2012; Kittel and Sole, 2015; Do Couto et al ., 2018; Santana et al ., 2019). However, some species are specialist predators (Menin et al ., 2015; Do Couto et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, some species are specialist predators (Menin et al ., 2015; Do Couto et al ., 2018). The feeding habit and diet of amphibians may be influenced by seasonal availability and abundance of food (Crnobrnja-Isailovic et al ., 2012), presence of competitors, and predation risk (Lopez et al ., 2009; Kittel and Sole, 2015; Santana et al ., 2019). Therefore, the ability of an individual amphibian to safely harvest and process sufficient quality food may vary with environmental differences.…”
Section: Introductionmentioning
confidence: 99%
“…The weight percentage (W%) was estimated as the total weight of each prey taxon divided by the combined estimated total weight of all prey taxa, multiplied by 100. The index of relative importance was calculated as: IRI = (N% + W%) FO%, where N% = numerical percentage, W% = weight percentage, and FO% = percentage of frequency of occurrence ( Martin, Twigg & Robinson, 1996 ; Hart, Calver & Dickman, 2002 ; Marti, Bechard & Jaksic, 2007 ; Santana et al, 2019 ; Muñoz-Pedreros & Rau, 2020 ; Rocha, Branco & Barnilli, 2021 ). The IRI was divided by the total IRI, then multiplied by 100 to obtain the percent IRI (IRI%).…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…Rubbo & Kiesecker, 2005;Smallbone et al, 2011;Westgate et al, 2015;Konowalik et al, 2020), the impact of urban habitat modification on anurans' feeding ecology has been less studied (Kovács et al 1995, López et al, 2015. In particular, studies on the trophic ecology of amphibians in the tropics are rare (Santana et al, 2019;Ofori et al, 2021). Urbanization leads to changes in microclimate, water balance, water quality, hydrology of wetlands and adjacent habitats, and to pollution increase and stress.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increases in ant populations because of damming did not lead to increased consumption in tree frogs (López et al, 2015). Based on dietary analysis of 57 individuals of the rufous frog Leptodactylus fuscus (family Leptodactylidae) in Brazil, Santana et al (2019) demonstrated that urban frogs focussed on eating Coleoptera while rural frogs had a more diverse diet. To complicate matters, feeding plasticity may not be linked to the relatedness between species as it may significantly differ between closely related species (López et al, 2015).…”
Section: Introductionmentioning
confidence: 99%